The Relationship between Choroidal Thickness and Intracellular Oxidised-reduced Glutathione and Extracellular Thiol–disulfide Homeostasis at Different Stages of Diabetic Retinopathy - Alışık, Murat; Işik, Mehmed Uğur (Informa UK Limited, 2020)
Purpose: To evaluate the relationship between diabetic retinopathy and oxidative damage by measuring intracellular and extracellular thiol levels, and to compare intracellular and extracellular thiol levels. Method: In this prospective, cross-sectional, and comparative study, 25 healthy control participants (group 1), a total of 25 diabetic macular edema (DME) patients with non-proliferative diabetic retinopathy (DRP) and without DME (group 2), and 25 DME patients with non-proliferative DRP and with DME (group 3) were included. Choroidal thickness (ChT) and central macular thickness (CMT) were measured by spectral domain optic coherence tomography. For the evaluation of antioxidant/oxidant balance, intracellular GSH (reduced glutathione) and GSSG (oxidized glutathione), extracellular SH (thiol) and SS (disulfide) levels were measured and recorded. Results: Comparing intracellular and extracellular thiol levels between groups, intracellular GSSG level and GSSG/GSH percent ratio, and extracellular disulfide and SS/SH percent ratio values were higher in diabetic patients than healthy participants. Choroidal thicknesses were significantly thinner in DRP groups compared to the healthy population. When the relationship between choroidal thicknesses and thiol levels was investigated, there were significant relationships between choroidal thicknesses and thiol levels in group 3. Conclusion: Oxidative stress and impaired intracellular GSH/GSSG and serum SH/SS balances were observed to have an effect on DRP and DME pathogenesis. In addition, in groups with and without DME, thinning in choroidal thicknesses and the relationship between these thicknesses and intra/extracellular oxidative stress indicators can also be explained.
Keywords: Male; Diabetic Retinopathy; Choroid; Choroidal Thickness; Visual Acuity; Middle Aged; Glutathione; Oxidative Stress; Cross-Sectional Studies; Thiol–disulfide; Reduced Glutathione; Homeostasis; Humans; Female; Prospective Studies; Sulfhydryl Compounds; Oxidized Glutathione; Disulfide Balance; Tomography, Optical Coherence; 3. Good health